Modeling, analysis and control of wireless power transfer systems - Chen, Bolantian (Nanyang Technological University, 2022)
Wireless Power Transfer （WPT） is being widely studied and discussed by researchers all over the world in terms of various technical points as an emerging and promising technology to be very in-depth studied for a wide range of applications and industries. Nowadays, electric vehicles are widely developed which is one of the major application scenarios of wireless energy charging is to charge electric vehicles, making them free from the limitation of low battery mileage. This includes both static wireless energy charging and dynamic wireless energy charging. These applications make good use of the characteristics of WPT: safety, durability, portability, and convenience. In this dissertation, the objective is to perform the mathematical modeling of a WPT system and design a feedback controller for the WPT system, including the derivation and simulation of the mathematical model, as well as the design and simulation of the control system, and finally to verify the accuracy of the model derivation and the feasibility and stability of the control system by building an experimental prototype in the laboratory, which is a 100W WPT system, to achieve a stable and accurate power control. Also, the literature review on the basic principles of WPT and circuit design and other related aspects are studied and the characteristics and transmission laws of the WPT circuit is provided. Besides, the parameters of the coils were calculated and simulated, and physical test results were measured by Bode 100. The final experimental results meet the design requirements and are also consistent with the model simulation results, which verifies the accuracy of the mathematical model and the feasibility and stability of the control system.